SENSIBILITE DU PRIX DE CIMENT AUX FLUCTUATIONS DU TAUX DE CHANGE DE FRANC CONGOLAIS PAR RAPPORT AU DOLLAR AMERICAIN A KINDU DE 2011 A 2020 - Charles, NDJADI LODI (IJRDO - Journal of Business Management, 2022)
In performing this research, the man concern is to verify whether the price of cement in Kindu is significantly influenced or not by fluctuations in the exchange rate of the congolese franc against the american dollar.From the statistical processing of our data, we understand that the price of cement in Kindu objects only the law of supply and demand, and that fluctuations in the exchange rate of the congolese franc against the american dollar have no significant influence.